2007
DOI: 10.1097/mao.0b013e318068b2dd
|View full text |Cite
|
Sign up to set email alerts
|

Positive Experiences Associated With Ménière's Disorder

Abstract: Most individuals with Ménière's disorder are able to identify a number of positive experiences associated with the condition. Understanding and having knowledge of these positive experiences help the patients cope with chronic conditions such as Ménière's disorder. Promotion of positive experiences may form a key element to better adjustment to the different symptoms and provide a key element for successful peer support program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The questionnaire about the positive experiences associated with M é ni è re ' s disorder comprised 27 questions, eighteen were derived from our earlier qualitative study on M é ni è re ' s disorder (Stephens et al, 2007). This was supplemented by three each on hearing problems, tinnitus, and balance problems derived from the separate studies on those symptoms (Stephens & Kerr, 2003;Kentala et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire about the positive experiences associated with M é ni è re ' s disorder comprised 27 questions, eighteen were derived from our earlier qualitative study on M é ni è re ' s disorder (Stephens et al, 2007). This was supplemented by three each on hearing problems, tinnitus, and balance problems derived from the separate studies on those symptoms (Stephens & Kerr, 2003;Kentala et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…This was supplemented by three each on hearing problems, tinnitus, and balance problems derived from the separate studies on those symptoms (Stephens & Kerr, 2003;Kentala et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…multiple sclerosis, cancer) have been able to identify some positive life and clinical experiences (Phillips & Stuifbergn, 2008;LaFortune, 1995). Our studies suggest that people with hearing and balance disorders are able to identify similar positive experiences as a result of their condition (Stephens & Kerr, 2003;Stephens et al, 2007). Signifi cant others (SOs) of patients with hearing and balance disorders can have a major effect in helping the patients accept and adapt to their condition and seek appropriate help (Manchaiah et al, 2012;Long & Bennett, 2009).…”
mentioning
confidence: 88%
“…interview followed by completion of a questionnaire). In a study on people with chronic M é ni è re ' s disorder conducted in Finland we found that patients were able to identify positive experiences derived from their condition (Stephens et al, 2007). M é ni è re ' s disorder is an idiopathic condition comprising repeated episodes of vertigo, fl uctuant hearing loss, tinnitus, and a sensation of pressure in the ear.…”
Section: Disorder Main Themes Of Positive Experiencesmentioning
confidence: 99%